2015
DOI: 10.1016/j.actbio.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Bone tissue engineering via human induced pluripotent, umbilical cord and bone marrow mesenchymal stem cells in rat cranium

Abstract: Human induced pluripotent stem cells (hiPSCs) are an exciting cell source with great potential for tissue engineering. Human bone marrow mesenchymal stem cells (hBMSCs) have been used in clinics but are limited by several disadvantages, hence alternative sources of MSCs such as umbilical cord MSCs (hUCMSCs) are being investigated. However, there has been no report comparing hiPSCs, hUCMSCs and hBMSCs for bone regeneration. The objectives of this pilot study were to investigate hiPSCs, hUCMSCs and hBMSCs for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 73 publications
1
120
1
Order By: Relevance
“…Our recent study showed that osteoinduced iPSMSCs seeded on pre-formed CPC scaffolds in rat cranial defects had comparable in vivo bone regeneration capability to BMSCs and umbilical cord MSCs (UCMSCs), but significantly higher than CPC control [25]. No teratoma was found during a 12 week observation [25].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study showed that osteoinduced iPSMSCs seeded on pre-formed CPC scaffolds in rat cranial defects had comparable in vivo bone regeneration capability to BMSCs and umbilical cord MSCs (UCMSCs), but significantly higher than CPC control [25]. No teratoma was found during a 12 week observation [25].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing effect on bone regeneration in the rat cranium among human IPSCs, human umbilical cord MSCs and human bone marrow MSCs, no significant differences were found in the amount of new bone [19]. Application of cell-free biofunctionalized macroporous calcium phosphate cement (CPC), used as a control in the same study, resulted in half or less than half amount of regenerated bone and the new blood vessel density was lower.…”
Section: Are Some Cells Better Than the Others?mentioning
confidence: 78%
“…We hypothesized that the hTMSCs differentiate into keratocyte progenitor cells, which have multipotent ability, similar to CSSC character [40]. To identify the multipotent ability of hTMSCs that had been treated with KDM, hematopoietic and MSC markers were measured.…”
Section: Discussionmentioning
confidence: 99%